PENCIPTAAN OPENING THEME SONG "HEROES OF JUSTICE" UNTUK FILM ANIMASI 2D "YAMATO KNIGHT OF JUSTICE" - Arin Patria Lingga, - (2020)
ABSTRACT The industrial revolution 4.0 has had a significant impact on the world of 2D animated films, especially Japan and the United States, both in terms of quality and quantity. This causes the mass media to be flooded with 2D animated films of the two countries with their own characteristics. 2D animated films are not only 2D animated visuals, but also OTS (opening theme song). Indonesian 2D animated films are not as big as Japan and America, they are still relatively small. However, its development has been significant from year to year. Seeing this phenomenon, the writer wants to contribute to the world of Indonesian 2D animated films, namely by creating an OTS (opening theme song) for the animated film "Yamato Knight of Justice" entitled "Heroes of Justice" along with 2D animation visuals for opening credits. The creation stage, we involve two stages of creation of the work at once based on a predetermined concept. Dimuali of the creation of the OTS (opening theme song) which worked on by the author, after that, the 2D animation visuals for the opening credits were worked on by the author and animator (Muhammad Rizky Sukma Ridha) by utilizing the means of the 4.0 industrial revolution which includes hardware and software. The end result is the opening credits work of the 2D animated film "Yamato Knight of Justice" with its OTS (opening soundtrack). entitled "Heroes of Justice." With this work, the writer hopes to make a small, meaningful contribution to the world of Indonesian 2D animated films. Keywords: 2D animated and opening theme song.